Social Interaction among Religious Members in the Taekwondo Sibayak Club Organization - Sindi Septi Claudia Siregar (TALENTA Publisher, 2024)
The purpose of this research is to determine the social interactions between religious communities that exist in a social organization, namely the Taekwondo Sibayak Club Organization. This research uses an ethnographic research method with a qualitative approach. This type of research is a case study, which is analytical-descriptive in the form of written words or direct quotations from observed speech and behavior. Researchers used data collection techniques in the form of observations carried out to observe behavior and phenomena that occurred in the Sibayak Club Taekwondo Organization. Researchers also conducted in-depth interviews using previously prepared methods and documentation. The results of this research show that social interaction between religious communities in the Taekwondo Sibayak Club Organization is established through activities and activities between followers of the Christian and Islamic religions such as sharing takjil, affirming sidi, breaking the fast, carrying out evening prayers, church services, New Year's gatherings, Eid al-Fitr gatherings, weddings, mourning, thanksgiving for entering a new house, and praying according to one's own beliefs.